SISTEM MONITORING DAN PENDETEKSI DINI KUALITAS UDARA BERDASARKAN PARAMETER CO DAN CO2 BERBASIS IoT - Ikhsan, Ridhotu Nur; Wibowo, Lastoni (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2025)
The increasing number of motor vehicles in urban areas causes a decline in air quality due to emissions such as carbon monoxide (CO) and carbon dioxide (CO₂). If left unchecked, similar conditions may occur in Cepu City. This research developed an air quality monitoring and early warning system based on the Internet of Things (IoT) using an MQ-135 sensor to detect CO and CO₂ and a DHT22 sensor for temperature and humidity. The collected data are transmitted to the Thingspeak platform and sent to users via Telegram notifications. The device was tested for seven days at two different locations in Cepu. The results show that the system can provide real-time air quality information and early warnings to help the public take precautions against air pollution impacts